Effects of Rustamiyah treatment plant effluent on concentration of some heavy metals in water and sediment of Diyala river - Musa, S.A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Concentrations  of  four  heavy  metals, Zinc , Copper , Lead  and  Cadimium  were  determed  in  water  and  sediment  samples   collected bi-weekly  from  six  sampling sites  on  the  lower  part  of  River  Diyala    during  low  flow  period  (August  to  October)  and   high  flow  period  (April  to  June). A  reference  point site (1)  was  situated   upstream the  effects  of  the  effluent. Present  work  describes  the  effect  of  Rustamiya  waste  water  treatment  plant  on heavy metals  in  water  and  sediment  of  River  Diyala.                                       The  results  indicated  that  heavy  metals  level  were  higher  in  low  flow  period  of  water  compared  with high flow period.Pb  concentration  was  high  in treatment  effluent site  compared with mixing  zone  and  reference  point. Cd level in  low  flow  period  in  water  was  high  and  affected  by  the  effluent  disposal  from  the  treatment  plant.                                          Concentration  of heavy  metals  in  sediment  showed  simple  difference  between  both  periods  in  refrence  point  and  mixing  zone. Average  Cu  concentration  in the  sediment  for  two  periods  was high in mixing zone compared with other metal